Food texture design and optimization - Dar, Yadunandan Lal; Light, Joseph (Chichester, West Sussex : Wiley-Blackwell, 2014)
'Due to the many problems that need to be solved to optimize food texture,the design and optimization of food texture is an ongoing challenge for the food industry. This unique 2-volume resource offers practical solutions to the complex and varied problems encountered in designing, measuring and optimizing food texture. The first volume presents insightful case studies on formulating products from a broad variety of food segments, such as cheese, soups, chocolate, cookies, brownies, bread, gluten-free products, low-fat/non-fat dairy products and more. The second volume provides an overview of the latest advances in food texture design and optimization'--
Includes bibliographical references and index.
Keywords: Food texture